"I Cannot Fall Pregnant!": Unequal Bodies in South African Higher Education. Issue 1 (1st March 2023) - Heyes, Kim; Brahic, Benedicte; Ramnund-Mansingh, Aradhana; Ingram, Nicola; Arun, Shoba; Seedat-Khan, Mariam
Abstract: Girls from single-parent households in South Africa (90 percent of whom are Black African or coloured) have significantly lower educational outcomes than other demographics. Through a methodology of life-history interviews, we explore the experiences of 30 women in single-headed households who have been successful in their educational endeavours as university students or graduates. Results show that pressures on girls from single-headed households to look after the family and domestic sphere and to protect their bodies from sexual abuse leave many girls depleted of the time, energy, and mental capacity required to study. Despite these challenges, these participants have escaped the perceived weight of their female burden in a post-apartheid, patriarchal society and reclaim their bodies and sense of agency through educational success.